2013
DOI: 10.1002/oby.20042
|View full text |Cite
|
Sign up to set email alerts
|

Effects of taspoglutide on glycemic control and body weight in obese patients with type 2 diabetes (T‐emerge 7 study)

Abstract: Objective: Therapies that lower blood glucose and provide weight loss may provide meaningful benefits for obese patients with type 2 diabetes mellitus (T2DM). This study assessed the efficacy of taspoglutide compared with placebo on glycemic control and weight in obese patients with T2DM inadequately controlled with metformin monotherapy. Design and Methods: In a 24-week, randomized, double-blind, placebo-controlled, multicenter trial, obese adults with T2DM were randomized (1:1) to weekly subcutaneous taspogl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…There are trials examining exenatide in the treatment of obesity; however, evidence supporting the weight‐loss effects of the other GLP‐1RAs relate to trials in T2D in which weight loss was not the primary endpoint. A summary of studies into the effects of GLP‐1RAs on weight loss in participants with and without diabetes is shown in Table .…”
Section: Therapeutic Applications Of Glp‐1ras In Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…There are trials examining exenatide in the treatment of obesity; however, evidence supporting the weight‐loss effects of the other GLP‐1RAs relate to trials in T2D in which weight loss was not the primary endpoint. A summary of studies into the effects of GLP‐1RAs on weight loss in participants with and without diabetes is shown in Table .…”
Section: Therapeutic Applications Of Glp‐1ras In Obesitymentioning
confidence: 99%
“…These GLP‐1RAs have demonstrated secondary weight benefits in trials in T2D, which were primarily focussed on the assessment of glycaemic control (Table ). Despite the fact that weight loss was not the main focus of the trials presented within Table , statistically significant weight losses were observed with lixisenatide and taspoglutide . Greater weight loss was also observed with albiglutide and dulaglutide vs. placebo, and while these results did not achieve statistical significance, this is likely to reflect study design and smaller treatment groups, rather than lack of effect.…”
Section: Therapeutic Applications Of Glp‐1ras In Obesitymentioning
confidence: 99%
“…After excluding duplicates and screening references on the basis of title and abstract, 123 relevant references were identified and examined in full text. Sixty‐seven of these publications fulfilled the inclusion criteria and were included in the analysis .…”
Section: Resultsmentioning
confidence: 99%
“…Of the 67 included RCTs, 18 investigated the efficacy of GLP‐1ra (six examined exenatide , three liraglutide , five lixisenatide , one dulaglutide and three taspoglutide ), 34 examined DPP‐4i (eight sitagliptin , 10 vildagliptin , seven saxagliptin , four alogliptin , five linagliptin ) and 15 researched SGLT‐2i (eight dapagliflozin , four canagliflozin , three empagliflozin ). All included trials were published in English.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation